PENGEMBANGAN MEDIA PEMBELAJARAN BUKU CERITA FLIPBOOK BERBASIS DIGITAL PADA MATERI PECAHAN UNTUK MENINGKATKAN KEMAMPUAN LITERASI MATEMATIS SISWA KELAS IV SD - Laura Carla Aritonang; Dini Ramadhani; Bunga Mulyhati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Based on the results of observations conducted by researchers in class IV of SD Negeri 8 Langsa, it was found that when learning media was not fully used, learning more often used textbooks and picture media. This study aims to develop a learning media product based on digital flipbook storybooks in Mathematics Learning, especially Fraction material for class IV of elementary school. This research is a type of R&D research and development with the ADDIE model consisting of five stages, namely Analysis, Design, Development, Implementation, and Evaluationi". The results of practitioners from teacher response questionnaires and student responses, teacher responses obtained a percentage of 97.14% with the criteria "very practical" and student responses found a percentage of 93.65% with the criteria "very practical". As for student learning outcomes by conducting a Normality test (N-Gain) of 70.10% with the criteria "effective". From the results of the assessment of digital-based flipbook storybook media, it can be concluded that digital-based flipbook storybook learning media in class IV Mathematics learning is very feasible to be applied for learning